Teachers’ Views on The Use of Chatbots to Support English Language Teaching in a Mobile Environment - Kee-Man Chuah (Kassel University Press, 2021)
The development in machine learning has allowed chatbots to be widely applied into educational settings. However, limited study has investigated teacher’s views on its usage for teaching and learning. This paper reports an exploratory study on English as a Second Language (ESL) teachers’ views with regards to the use of chatbots for their teaching and learning delivery in a mobile environment. Using survey research design, views from 142 ESL teachers were gathered using questionnaires, which consist of Likert-scale items and open-ended questions. The teachers were sampled using purposive sampling method. The items and questions were developed based on the principles of the Community of Inquiry (CoI) framework, which focuses on social, cognitive and teaching presence. Data from the Likert-scaled items were analyzed using descriptive statistics while open-ended questions were coded thematically. The findings showed that teachers perceived the use of chatbots in giving feedback to their students as very helpful though some of them needed extra training on how to use them. They also thought chatbots can simulate an interaction cycle for students to practice the tar-get language. In addition, the teachers believed chatbots augmented a greater level of social presence, which eventually creates an environment for their students to be active. All in all, the findings provided valuable insights on the proper integration of chatbots in teaching and learning while gauging essential affordances and constraints of its use from ESL teachers’ perspective.